SIFAT PAPAN SERAT DARI DELAPAN JENIS KAYU INDONESIA BAGIAN TIMUR (Fibreboard Properfies from Eight East Indonesian Wood Species) - Setyani B Lestari; Rena M Siagian (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
This paper deals with on experiment of fibreboard from eight East Indonesian wood species. Wood pulp was cooked by semi chemical process with hot caustic soda. The cooking conditions were concentration of alkali 35 g/l, wood to liquor ratio 1 : 8 and temperature at 100°C for 2 hours. Sheet was formed by wet felting technique using deckle box, followed by cold pressing at the pressure Of 10,kg/cm2 for 5 minutes. Wet fibreboard sheet then hot pressed at the pressure of 25 kg/cm2 for 10 minutes 170°C.The results shows. that the fibreboard density and modulus. of rupture from seven wood species meet the requirements of FAO standard. only fibreboard from one wood species which meet FAO standard for modulus of elasticity Fibreboard from three wood species meet the standard for tensile strength. Fibreboard from eight wood species don't meet FAO standard for water absorption and thicknessling swelling.